Transcriptomic gene-network analysis of exposure to silver nanoparticle reveals potentially neurodegenerative progression in mouse brain neural cells. (August 2016) - Lin, Ho-Chen; Huang, Chin-Lin; Huang, Yuh-Jeen; Hsiao, I-Lun; Yang, Chung-Wei; Chuang, Chun-Yu
Abstract: Silver nanoparticles (AgNPs) are commonly used in daily living products. AgNPs can induce inflammatory response in neuronal cells, and potentially develop neurological disorders. The gene networks in response to AgNPs-induced neurodegenerative progression have not been clarified in various brain neural cells. This study found that 3–5 nm AgNPs were detectable to enter the nuclei of mouse neuronal cells after 24-h of exposure. The differentially expressed genes in mouse brain neural cells exposure to AgNPs were further identified using Phalanx Mouse OneArray® chip, and permitted to explore the gene network pathway regulating in neurodegenerative progression according to Cytoscape analysis. In focal adhesion pathway of ALT astrocytes, AgNPs induced the gene expression of RasGRF1 and reduced its downstream BCL2 gene for apoptosis. In cytosolic DNA sensing pathway of microglial BV2 cells, AgNPs reduced the gene expression of TREX1 and decreased IRF7 to release pro-inflammatory cytokines for inflammation and cellular activation. In MAPK pathway of neuronal N2a cells, AgNPs elevated GADD45α gene expression, and attenuated its downstream PTPRR gene to interfere with neuron growth and differentiation. Moreover, AgNPs induced beta amyloid deposition in N2a cells, and decreased PSEN1 and PSEN2, which may disrupt calcium homeostasis and presynaptic dysfunction for Alzheimer's disease development. These findings suggested that AgNPs exposure reveals the potency to induce the progression of neurodegenerative disorder. Highlights: AgNPs can cross the cell membrane to nucleus of mouse neuronal cells. AgNPs disturbed focal adhesion, cytosolic DNA sensing and MAPK pathway. AgNPs induced Aβ, and reduced PSEN1 and PSEN2 for neurodegenerative disorders. AgNP exposure potentially induced the progression of AD disorder.